(untitled) (Research, Society and Development, 2022)
Health care in sickle cell disease must include interdisciplinary practices based on the unique needs of subjects in order to promote efficient and quality care. Indeed, the objective was to unveil care practices in people with sickle cell disease. Qualitative study, carried out in the city of Fortaleza, in six Primary Health Care Units, a Coordinating Blood Center and a tertiary hospital that monitors patients with sickle cell disease. Based on the discourses of health workers and users, three essential analytical categories emerged: “Diagnosis of sickle cell disease”, “Care practices for people with sickle cell disease” and “Reorganization of the service in the face of the pandemic”. Care practices for people with sickle cell disease are carried out in specialized care, through periodic consultations, with access to the multidisciplinary team, which promotes the formation of bonds with users, favoring greater adherence to treatment, as well as a positive perception about the therapy instituted. A reorganization of the health service was noticed in order to maintain the continuity of care during the pandemic, reducing the rate of complications caused by the lack of health care.